2020
DOI: 10.1002/pmic.201900324
|View full text |Cite
|
Sign up to set email alerts
|

Deadly Proteomes: A Practical Guide to Proteotranscriptomics of Animal Venoms

Abstract: Animal venoms are renowned for their toxicity, biochemical complexity, and as a source of compounds with potential applications in medicine, agriculture, and industry. Polypeptides underlie much of the pharmacology of animal venoms, and elucidating these arsenals of polypeptide toxins—known as the venom proteome or venome—is an important step in venom research. Proteomics is used for the identification of venom toxins, determination of their primary structure including post‐translational modifications, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 172 publications
(231 reference statements)
0
23
0
Order By: Relevance
“…Venom Comprises a Diverse Array of Peptide Toxins. Previous studies of caterpillar venom relied on crushed extracts of spines or spicules, but such extracts invariably contain cellular and cuticular material, which complicates identifying venom components using transcriptomic and proteomic workflows (19). To overcome this obstacle, we obtained venom by gently pressing parafilm supported on a wire loop to the tips of venom spines.…”
Section: Resultsmentioning
confidence: 99%
“…Venom Comprises a Diverse Array of Peptide Toxins. Previous studies of caterpillar venom relied on crushed extracts of spines or spicules, but such extracts invariably contain cellular and cuticular material, which complicates identifying venom components using transcriptomic and proteomic workflows (19). To overcome this obstacle, we obtained venom by gently pressing parafilm supported on a wire loop to the tips of venom spines.…”
Section: Resultsmentioning
confidence: 99%
“…The dominance of smaller molecular masses and peptides, with often unknown physiological effects, described in only parts of the Old World vipers, shows that peptidomics of the non-classically defined toxins families is still an emerging field [ 198 ]. In particular, the combination with TD measurements or intact mass profiling (IMP) can compensate for existing gaps and give a detailed view on the venom content in the low molecular mass range [ 52 , 53 ].…”
Section: Venom Variations Of Old World Vipersmentioning
confidence: 99%
“…The integration of high-resolution mass spectrometry (MS)-based workflows, mostly in combination with preceding decomplexation steps, plays a decisive role and has continuously developed over the past decades [ 51 ]. Today, de novo and database-dependent annotation methods allow the identification of toxin families, individual toxins, and various proteoforms requiring only minute quantities of venom [ 52 ]. In particular, the TD approach is on the rise and allows precise toxin identification directly from crude venoms and in this context the applicability of Fourier transform ion cyclotron resonance (FT-ICR) MS most likely will constitute a decisive step in the coming years [ 49 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our mass spectrometry analysis revealed that the expression batch of USCTX was almost exclusively composed of peptide pairs displaying aberrant cysteine crosslinking or peptides that lack disulfide bonds. Only a single peptide with m / z 1215.56, matching the C2-C5 crosslink of native USCTX, was identified via MALDI and even more sensitive Orbitrap experiments [ 27 , 28 , 29 ]. Our data suggest that the cell-free system faces difficulties in facilitating the correct disulfide bond formation in such heavily cysteine-crosslinked peptides.…”
Section: Resultsmentioning
confidence: 99%
“…For mass spectrometry, we used the highly sensitive Orbitrap instrument on which we previously identified other ICK components [ 28 , 29 ]. Briefly, 0.5 µg of each sample in 0.1% formic acid (Sigma-Aldrich) was loaded onto a 50 cm µPAC C18 column (Pharma Fluidics, Gent, Belgium) mounted on an UltiMate 3000RSLCnano (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%